2014
DOI: 10.1073/pnas.1406413111
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling translocation intermediates of RNA polymerase

Abstract: Translocation of RNA polymerase (RNAP) is a robust target for regulation of gene expression in prokaryotes and eukaryotes (1-3). During elongation, RNAP frequently encounters a broad range of DNA/RNA conformations (RNA hairpins, curved and cruciform DNA), DNA-binding proteins, DNA lesions, and misincorporation events at the 3′ ends of the RNA. These encounters impede forward translocation, leading to RNAP pausing (3). There are many protein factors that strengthen or weaken pausing by targeting translocation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…We previously suggested that increased flexibility of the dCMP sugar-phosphate backbone of a CpG dinucleotide in the template DNA strand can cause pausing by interfering with proper alignment of the template DNA base with incoming NTP in the post-translocated state [ 1 , 33 ]. Similar misalignment of the 3′ RNA end with the template base may cause pausing in the pre-translocated state [ 1 , 12 , 68 ]. This dynamic property of CpG in DNA has been identified by a variety of methods [ 69 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously suggested that increased flexibility of the dCMP sugar-phosphate backbone of a CpG dinucleotide in the template DNA strand can cause pausing by interfering with proper alignment of the template DNA base with incoming NTP in the post-translocated state [ 1 , 33 ]. Similar misalignment of the 3′ RNA end with the template base may cause pausing in the pre-translocated state [ 1 , 12 , 68 ]. This dynamic property of CpG in DNA has been identified by a variety of methods [ 69 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent MD simulation connecting a large number of short trajectories to a network of Markov states demonstrated that the translocation of Pol II happens at ∼20 μs [48], which is much faster than the milliseconds single molecule measurements. The simulated translocation, however, does not involve TL opening transition, and only contains a minimum scaffold of transcription complex [54]. In addition, MD simulation studies had also shown that the TL only slightly opens after a fast PPi release at microseconds [43,44], while the substantial opening of the TL is left to happen thereafter.…”
Section: Discussionmentioning
confidence: 98%
“…According to the MSM, the overall translocation rate was estimated to be about tens of microseconds at least, which is very fast comparing to the rate--limiting step of the elongation cycle (tens of milliseconds). Including the full transcription bubble may slow down the translocation rate 86 . One noted that the translocation was simulated with a trigger loop in an open conformation 85 , which had been suggested to be a pre--requisite for the translocation to happen 87,88 .…”
Section: Probing Molecular Details Of Mechano--chemical Couplinmentioning
confidence: 99%
“…Anyhow, including the full transcription bubble may slow down the translocation rate. [88] In addition, it has been noted that the translocation is simulated with a trigger loop (TL) in an open conformation already. [87] The TL open has been suggested to be a pre-requisite for the translocation to happen.…”
Section: Probing Molecular Details Of Mechano-chemical Coupling and F...mentioning
confidence: 99%